A lithium nickel manganese oxide positive electrode material and preparation method thereof and battery
By introducing the rock salt phase into the nickel-manganate positive electrode material and performing specific sintering and grinding steps, the problem of poor circulation performance of the nickel-manganate positive electrode material is solved, and higher circulation and storage performance is achieved, which is suitable for high-power lithium-ion batteries.
Patent Information
- Application Number
- CN202411943712.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The cycling performance of the lithium nickel manganate cathode material used in existing lithium-ion batteries is poor and cannot fully meet the requirements of high power. It is mainly due to the disproportionation reaction of Mn3+ that leads to the generation of Mn2+ and Mn4+, destroying the positive electrode-electrolyte interface and hindering ion transmission.
By mixing the nickel-manganese precursor with a lithium source and dopant, the first sintering is performed to generate lithium nickel-manganese oxide containing the lithosaic phase, followed by airflow grinding and second sintering, the oxygen defects are repaired and the lithosaic phase is cured, improving the chemical and structural stability of the material.
The circulation and storage performance of the nickel-manganate lithium co-electrode material is improved, the dissolution of Mn is slowed, the tolerance to HF corrosion and electrolyte corrosion is enhanced, and the high power demand is met.
Smart Images

Figure CN119370911B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium nickel manganese oxide positive electrode material and a preparation method thereof and a battery. Background Art
[0002] Cathode materials are the decisive factors affecting electrochemical performance, and play a leading role in battery capacity, energy density and cycle performance. Therefore, developing high energy density cathode materials is an important means to break the energy limitation of current lithium-ion batteries.
[0003] According to the working principle of lithium-ion batteries, the specification capacity and working voltage of the positive electrode material directly affect the energy density of lithium-ion batteries. Therefore, using high-capacity or high-working-voltage positive electrode materials to increase the energy density of lithium-ion batteries is an effective way to break through this limitation.
[0004] Spinel LiNi 0.5 Mn 1.5 O4 (LNMO) has an ultra-high discharge platform of 4.7V (vs. Li / Li + ), and has a high energy density of 650Wh / kg, which is 1.63 times and 1.31 times that of LiMn2O4 and LiFePO4. Therefore, high-voltage LNMO with a spinel structure is considered to be one of the most promising cathode materials for next-generation lithium-ion batteries in terms of high energy density, abundant raw materials, and large-scale production potential.
[0005] Despite these advantages, bulk LNMO cannot fully meet the requirements of high power due to its poor cycling performance. 2+ The presence of Mn in LNMO 3+ The content of Mn decreases sharply, but there is still some 3+ , these Mn 3+ During the battery charge and discharge cycle, a disproportionation reaction will occur to generate Mn 2+ and Mn 4+ Among them, Mn 4+ Remain in the lattice, while Mn 2+ It dissolves in the electrolyte and deposits on the surface of the negative electrode, which in turn destroys the positive electrode-electrolyte interface, accelerates the decomposition and diffusion of the electrolyte, and hinders the ion transmission channel. Due to the loss of some manganese, the LNMO material also has the Jan-Taylor effect, which causes the cycle performance to decline rapidly.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The object of the present invention is to provide a nickel-manganese-oxide lithium positive electrode material and a preparation method and a battery, so as to solve or improve the above technical problems.
[0008] The present invention can be implemented like this:
[0009] In a first aspect, the present invention provides a method for preparing a lithium nickel manganese oxide positive electrode material, the method comprising the following steps: mixing a nickel manganese precursor with a lithium source and a dopant, and then performing a first sintering to obtain lithium nickel manganese oxide containing a rock salt phase; air flow milling the lithium nickel manganese oxide containing a rock salt phase to obtain a lithium nickel manganese oxide single crystal fine powder; and performing a second sintering on the lithium nickel manganese oxide single crystal fine powder to obtain a lithium nickel manganese oxide positive electrode material;
[0010] The chemical formula of the nickel-manganese precursor is Ni x Mn y (OH)2, where x is 0.2~0.3, y=1-x; the chemical formula of the rock salt phase is Li m Ni 1-m O, where 0<m<1;
[0011] The dopant is selected from at least one of ZrO2, Cr2O3 and Y2O3, and the mass of the dopant is 0.5% to 5% of the nickel manganese precursor.
[0012] In an optional embodiment, the ratio of the molar amount of Li in the lithium source to the total molar amount of Ni and Mn in the nickel manganese precursor is 0.5:1 to 0.55:1.
[0013] In an alternative embodiment, the lithium source is lithium carbonate.
[0014] In an optional embodiment, the first sintering is performed at 1000° C. to 1200° C. for 8 h to 15 h;
[0015] The first sintering atmosphere is air.
[0016] In an optional embodiment, in the lithium nickel manganese oxide containing a rock salt phase obtained by the first sintering, the mass percentage of the rock salt phase is 2wt% to 10wt%.
[0017] In an optional embodiment, the jet milling is carried out under the conditions of a classification frequency of 115 Hz to 125 Hz and a pressure of 0.40 MPa to 0.50 MPa.
[0018] In an optional embodiment, the particle size of the lithium nickel manganese oxide single crystal fine powder obtained after the jet mill is D 50 5μm~7μm.
[0019] In an optional embodiment, the second sintering is performed at 700° C. to 900° C. for 1 h to 10 h;
[0020] The atmosphere for the second sintering was air.
[0021] In a second aspect, the present invention provides a lithium nickel manganese oxide positive electrode material, which is prepared by the preparation method of any one of the aforementioned embodiments;
[0022] In the lithium nickel manganese oxide positive electrode material, the rock salt phase is solidified on the surface of the lithium nickel manganese oxide single crystal fine powder.
[0023] In a third aspect, the present invention provides a battery comprising the lithium nickel manganese oxide positive electrode material of the aforementioned embodiment.
[0024] The beneficial effects of the present invention include:
[0025] The present invention can increase the chemical and structural stability of lithium nickel manganese oxide by mixing a nickel manganese precursor with a lithium source and a dopant and then performing the first sintering, while inducing oxygen defects to assist the formation of a rock salt phase. Among them, a larger doping amount of the dopant and a higher first sintering temperature are both conducive to the generation of oxygen defects, ultimately resulting in a higher content of rock salt phase impurities. The material obtained by the first sintering is subjected to air flow milling. These places where the rock salt phase is generated are also locations with uneven structures, which are easily broken under air flow milling to expose them; and after crushing, exposing more faces is conducive to the repair of oxygen defects and the reconstruction of the spinel structure during the second sintering, generating more uniform primary particles. In the subsequent second sintering, the spinel phase of lithium nickel manganese oxide can be fully repaired, absorbing oxygen atoms to fill most of the oxygen defects generated by the excessively high temperature of the first sintering, and at the same time, the more stable rock salt phase reacts very low at this temperature, and the second sintering can retain and solidify the rock salt phase. The rock salt phase has higher resistance to HF corrosion and electrolyte erosion than the LNMO spinel body. The presence of an appropriate amount of rock salt phase can slow down the dissolution of Mn, which is beneficial to improving the stability of Mn in LNMO and improving the cycle and storage performance of the battery prepared from the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 1;
[0028] Figure 2 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Comparative Example 1;
[0029] Figure 3 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Comparative Example 2;
[0030] Figure 4 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Comparative Example 3;
[0031] Figure 5 The XRD diagrams of the lithium nickel manganese oxide positive electrode materials prepared in Example 1 and Comparative Examples 1 to 3 are shown. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0033] The lithium nickel manganese oxide positive electrode material and its preparation method and battery provided by the present invention are specifically described below.
[0034] The conventional view in the current field is that the presence of the rock salt phase will destroy the orderly arrangement of Ni and Mn in the lattice. At the same time, the rock salt phase has low electrochemical activity and poor ion or electronic conductivity, which is not conducive to the capacity of LNMO. The inventor creatively discovered that although the presence of the rock salt phase can destroy the lattice arrangement, its resistance to HF corrosion and electrolyte erosion is significantly higher than that of the LNMO spinel body. The presence of an appropriate amount of rock salt phase can slow down the dissolution of Mn, which is beneficial to the stability of Mn in LNMO. Therefore, the inventor creatively proposed to form a rock salt phase in the first sintering stage, and then set up a suitable second sintering process to fill the oxygen defects generated when the rock salt phase is formed, and the rock salt phase can be solidified on the LNMO body. This method can maintain LNMO with better rate performance and has almost no effect on its electrical properties within the normal rate test range.
[0035] The preparation method of the lithium nickel manganese oxide positive electrode material provided by the present invention comprises the following steps: mixing a nickel manganese precursor with a lithium source and a dopant, and then performing a first sintering to obtain lithium nickel manganese oxide containing a rock salt phase; air flow milling the lithium nickel manganese oxide containing the rock salt phase to obtain lithium nickel manganese oxide single crystal fine powder; and performing a second sintering on the lithium nickel manganese oxide single crystal fine powder to obtain the lithium nickel manganese oxide positive electrode material.
[0036] The chemical formula of the nickel-manganese precursor is Ni x Mn y (OH)2, wherein x is 0.2-0.3, and y=1-x. In some typical embodiments, the chemical formula of the nickel-manganese precursor is Ni 0.25 Mn 0.75 (OH)2.
[0037] The chemical formula of the rock salt phase is Li m Ni1-m O, where 0<m<1.
[0038] In the present invention, the dopant is selected from at least one of ZrO2, Cr2O3 and Y2O3, that is, only any one of ZrO2, Cr2O3 and Y2O3 may be doped, or two or three of ZrO2, Cr2O3 and Y2O3 may be doped simultaneously.
[0039] It should be noted that the present invention specifically selects at least one of ZrO2, Cr2O3 and Y2O3 as a dopant, which can increase the chemical and structural stability of LNMO, and can also induce oxygen defects and assist the formation of rock salt phase.
[0040] The total mass of the dopant is 0.5% to 5% of the nickel manganese precursor, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., and can also be other values within the range of 0.5% to 5%.
[0041] Controlling the dopant within the above range is conducive to the generation of oxygen defects, and a higher content of rock salt phase can be obtained. However, if the dopant content is too high, such as more than 5%, it is easy to cause the dopant to be enriched on the positive electrode surface, seriously affecting the lithium ion transmission and significantly reducing the capacity.
[0042] In the present invention, the ratio of the molar amount of Li in the lithium source to the total molar amount of Ni and Mn in the nickel-manganese precursor is 0.5:1 to 0.55:1, such as 0.5:1, 0.51:1, 0.52:1, 0.53:1, 0.54:1 or 0.55:1, and can also be other values within the range of 0.5:1 to 0.55:1.
[0043] Among them, the lithium source is lithium carbonate.
[0044] In the present invention, the first sintering can be performed at 1000° C. to 1200° C. for 8 h to 15 h.
[0045] The temperature of the first sintering may be 1000°C, 1020°C, 1050°C, 1080°C, 1100°C, 1120°C, 1150°C, 1180°C or 1200°C, or other values within the range of 1000°C to 1200°C.
[0046] By controlling the temperature of the first sintering to be within the above range, a large amount of rock salt phase can be obtained.
[0047] The time of the first sintering may be 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, etc., or may be other values within the range of 8 h to 15 h.
[0048] The first sintering atmosphere is air.
[0049] In some embodiments, in the lithium nickel manganese oxide containing a rock salt phase obtained by the first sintering, the mass percentage of the rock salt phase is 2wt% to 10wt%, such as 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, etc., and can also be other values within the range of 2wt% to 10wt%.
[0050] In the present invention, the jet mill pulverization can be carried out under the conditions of a classification frequency of 115 Hz to 125 Hz and a pressure of 0.40 MPa to 0.50 MPa.
[0051] Among them, the graded frequency can be 115Hz, 116Hz, 117Hz, 118Hz, 119Hz, 120Hz, 121Hz, 122Hz, 123Hz, 124Hz or 125Hz, etc., or other values within the range of 115Hz~125Hz.
[0052] The pressure may be 0.4 MPa, 0.41 MPa, 0.42 MPa, 0.43 MPa, 0.44 MPa, 0.45 MPa, 0.46 MPa, 0.47 MPa, 0.48 MPa, 0.49 MPa or 0.5 MPa, etc., or other values within the range of 0.40 MPa to 0.50 MPa.
[0053] In some optional embodiments, the particle size of the lithium nickel manganese oxide single crystal fine powder obtained after the jet mill is D 50 It is 5μm~7μm, such as 5μm, 5.5μm, 6μm, 6.5μm or 7μm, and can also be other values within the range of 5μm~7μm.
[0054] It should be noted that the location where the rock salt phase is generated is a point with an uneven structure, which is easy to break under airflow milling, exposing it; on the other hand, after milling, more faces are exposed, which is conducive to the repair of oxygen defects and the reconstruction of the spinel structure during the second sintering, and the generation of more uniform primary particles. However, if the particle size of the lithium nickel manganese oxide single crystal fine powder obtained by airflow milling is too small, it is not conducive to the integrity of the particles, and it is easy to produce excessive micropowder, which deteriorates the cycle performance of the positive electrode material. At the same time, after over-milling, the primary particle structure will be seriously damaged, which is not conducive to the stability of the material body structure; if the particle size of the lithium nickel manganese oxide single crystal fine powder obtained by airflow milling is too large, it is not conducive to the exposure of multiple surfaces during the later sintering process, and the particles will stick together, which seriously affects the uniform generation of the rock salt phase on the LNMO positive electrode surface.
[0055] The second sintering can be carried out at 700°C~900°C for 1h~10h.
[0056] The temperature of the second sintering may be 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C or 900°C, or other values within the range of 700°C to 900°C.
[0057] By carrying out the second sintering under the above temperature conditions, the lithium nickel manganese oxide spinel phase can be repeatedly repaired and absorb oxygen atoms to fill most of the oxygen defects generated by the high temperature of the first sintering. At the same time, the more stable rock salt phase has a very low reactivity at the second sintering temperature, and the second sintering can retain and solidify the rock salt phase.
[0058] If the temperature of the second sintering is higher than 900°C, it is easy to cause serious agglomeration of the positive electrode particles. At the same time, the LNMO body will undergo a phase structure change side reaction, resulting in a large number of oxygen defects, which is not conducive to structural stability.
[0059] The time of the second sintering can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc., or other values within the range of 1 h to 10 h.
[0060] The atmosphere for the second sintering was air.
[0061] Correspondingly, the present invention also provides a lithium nickel manganese oxide positive electrode material, which is prepared by the above preparation method.
[0062] In the lithium nickel manganese oxide positive electrode material, the rock salt phase is solidified on the surface of the lithium nickel manganese oxide single crystal fine powder.
[0063] In addition, the present invention also provides a battery, which contains the above-mentioned lithium nickel manganese oxide positive electrode material.
[0064] The battery has good storage performance and cycle performance.
[0065] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0066] Example 1
[0067] This embodiment provides a lithium nickel manganese oxide positive electrode material, and the preparation method thereof includes:
[0068] S1: Mixing.
[0069] 1 kg of Ni 0.25 Mn 0.75 The (OH)2 precursor was uniformly mixed with 209 g of lithium carbonate and dopants (20 g of ZrO2 and 20 g of Cr2O3) to obtain a mixed material.
[0070] That is, the mass of the dopant is 4% of the nickel-manganese precursor, and the ratio of the molar amount of Li in the lithium source to the total molar amount of Ni and Mn in the nickel-manganese precursor is 0.51:1.
[0071] S2: First sintering.
[0072] The mixture was kept at 1100°C for 10 h to obtain lithium nickel manganese oxide (Li 0.5 Ni 0.25 Mn 0.75 O2). The heating rate of the first sintering is 3°C / min, and the sintering atmosphere is air.
[0073] S3: Jet mill crushing.
[0074] The primary sintered material was jaw crushed and then jet milled at a classification frequency of 120 Hz and a grinding pressure of 0.45 MPa to obtain monodisperse lithium nickel manganese oxide single crystal fine powder (D 50 is 6μm).
[0075] S4: Second sintering.
[0076] The crushed material was heated to 800°C in a box furnace and kept warm for 10 hours, and then sieved to obtain a lithium nickel manganese oxide positive electrode material. The heating rate of the second sintering was 3°C / min, and the sintering atmosphere was air.
[0077] Example 2
[0078] The difference between this embodiment and embodiment 1 is that the doping agent is 20 g of ZrO2 and 20 g of Y2O3.
[0079] Example 3
[0080] This embodiment provides a lithium nickel manganese oxide positive electrode material, and the preparation method thereof includes:
[0081] S1: Mixing.
[0082] 1 kg of Ni 0.25 Mn 0.75 The (OH)2 precursor is uniformly mixed with lithium carbonate and a dopant to obtain a mixed material. The dopant is Cr2O3 and Y2O3 in a mass ratio of 1:1.
[0083] That is, the mass of the dopant is 0.5% of the nickel-manganese precursor, and the ratio of the molar amount of Li in the lithium source to the total molar amount of Ni and Mn in the nickel-manganese precursor is 0.5:1.
[0084] S2: First sintering.
[0085] The mixture was kept at 1000°C for 15 h to obtain lithium nickel manganese oxide (Li 0.5 Ni 0.25 Mn 0.75 O2). The heating rate of the first sintering is 3°C / min, and the sintering atmosphere is air.
[0086] S3: Jet mill crushing.
[0087] The primary sintered material was jaw crushed and then jet milled at a classification frequency of 115 Hz and a grinding pressure of 0.4 MPa to obtain monodisperse lithium nickel manganese oxide single crystal fine powder (D 50 is 7μm).
[0088] S4: Second sintering.
[0089] The crushed material was heated to 700°C in a box furnace for 5 hours and sieved to obtain a lithium nickel manganese oxide positive electrode material. The heating rate of the second sintering was 3°C / min, and the sintering atmosphere was air.
[0090] Example 4
[0091] This embodiment provides a lithium nickel manganese oxide positive electrode material, and the preparation method thereof includes:
[0092] S1: Mixing.
[0093] 1 kg of Ni 0.25 Mn 0.75 The (OH)2 precursor is uniformly mixed with lithium carbonate and a dopant to obtain a mixed material. The dopant is Y2O3.
[0094] That is, the mass of the dopant is 5% of the nickel-manganese precursor, and the ratio of the molar amount of Li in the lithium source to the total molar amount of Ni and Mn in the nickel-manganese precursor is 0.55:1.
[0095] S2: First sintering.
[0096] The mixture was kept at 1200°C for 8 hours to obtain lithium nickel manganese oxide (Li 0.5 Ni 0.25 Mn 0.75 O2). The heating rate of the first sintering is 3°C / min, and the sintering atmosphere is air.
[0097] S3: Jet mill crushing.
[0098] The primary sintered material was jaw crushed and then jet milled at a classification frequency of 125 Hz and a grinding pressure of 0.5 MPa to obtain monodisperse lithium nickel manganese oxide single crystal fine powder (D 50 is 5μm).
[0099] S4: Second sintering.
[0100] The crushed material was heated to 900°C in a box furnace for 1 hour and sieved to obtain a lithium nickel manganese oxide positive electrode material. The heating rate of the second sintering was 3°C / min, and the sintering atmosphere was air.
[0101] Comparative Example 1
[0102] The difference between this comparative example and Example 1 is that the temperature of the first sintering is 900°C.
[0103] Comparative Example 2
[0104] The difference between this comparative example and Example 1 is that there is no air flow milling and the second sintering step, that is, only the lithium nickel manganese oxide containing the rock salt phase is obtained by the first sintering.
[0105] Comparative Example 3
[0106] The difference between this comparative example and Example 1 is that the temperature of the second sintering is 500°C.
[0107] Comparative Example 4
[0108] The difference between this comparative example and Example 1 is that no dopant is used.
[0109] Comparative Example 5
[0110] The difference between this comparative example and Example 1 is that the mass of the dopant is 8% of the nickel-manganese precursor.
[0111] Comparative Example 6
[0112] The difference between this comparative example and Example 1 is that the doping agent is 20 g of ZrO2 and 20 g of TiO2.
[0113] Comparative Example 7
[0114] The difference between this comparative example and Example 1 is that the doping agents are 20 g of Cr2O3 and 20 g of Al2O3.
[0115] Comparative Example 8
[0116] The difference between this comparative example and Example 1 is that the temperature of the first sintering is 1250°C.
[0117] Comparative Example 9
[0118] The difference between this comparative example and Example 1 is that the particle size of the lithium nickel manganese oxide single crystal fine powder obtained after the jet mill is D 50 is 2μm.
[0119] Comparative Example 10
[0120] The difference between this comparative example and Example 1 is that the particle size of the lithium nickel manganese oxide single crystal fine powder obtained after the jet mill is D 50 is 10μm.
[0121] Comparative Example 11
[0122] The difference between this comparative example and Example 1 is that after the first sintering, the second sintering is directly carried out without air flow grinding.
[0123] Comparative Example 12
[0124] The difference between this comparative example and Example 1 is that the temperature of the second sintering is 1000°C.
[0125] Test example
[0126] ①, taking Example 1 and Comparative Examples 1 to 3 as examples, the obtained lithium nickel manganese oxide positive electrode materials were observed by scanning electron microscope and characterized by XRD. The SEM images are as follows: Figures 1 to 4 The XRD results are shown in Figure 5 shown.
[0127] Depend on Figures 1 to 4 It can be seen that: using the sintering process provided in Example 1 of the present invention, single crystal particles with good dispersibility can be obtained, and the material surface is smooth, which is conducive to structural stability.
[0128] exist Figure 5 The peak at 43.5° in Example 1 is more obvious, indicating that the content of rock salt phase is significantly higher. The presence of these rock salt phases can significantly improve the ability of LNMO to resist HF corrosion and electrolyte erosion. The presence of an appropriate amount of rock salt phase can slow down the dissolution of Mn, which is beneficial to the stability of Mn in LNMO. At the same time, the buckling results also show that the cycle performance is better when the amount of rock salt phase is contained.
[0129] ②. The nickel-manganese-oxide lithium positive electrode materials obtained in Examples 1 to 4 and Comparative Examples 1 to 12 were used to make 2025 button batteries and perform electrochemical performance tests. The preparation and testing methods are as follows:
[0130] The ternary positive electrode is carbon black: PVDF = 90:5:5, the negative electrode is metallic lithium, the electrolyte is Xinzhoubang (M10), the charge and discharge voltage range is 3.5V~4.95V, and it is mainly charged and discharged once at different rates of 0.1C, 0.2C, 0.5C, and 1C. Finally, the 1C capacity and cycle performance are tested at room temperature. The results are shown in Table 1.
[0131] Table 1 Test results
[0132]
[0133] It can be seen from Table 1 that the nickel manganese oxide positive electrode material obtained in the embodiment can be more conducive to improving the battery's charge capacity and cycle retention rate than the nickel manganese oxide positive electrode material obtained in the comparative example.
[0134] In summary, the present invention can increase the chemical and structural stability of lithium nickel manganese oxide by mixing the nickel manganese precursor with the lithium source and the dopant for the first sintering, while inducing oxygen defects to assist the formation of the rock salt phase. Among them, a larger doping amount of the dopant and a higher first sintering temperature are conducive to the generation of oxygen defects, which ultimately lead to a higher content of rock salt phase impurities. The material obtained by the first sintering is subjected to air flow milling. These places where the rock salt phase is produced are also locations with uneven structures, which are easily broken under air flow milling, so that they are exposed; and, after crushing, exposing more faces is conducive to the repair of oxygen defects and the reconstruction of the spinel structure during the second sintering, generating more uniform primary particles. In the subsequent second sintering, the spinel phase of lithium nickel manganese oxide can be fully repaired, absorbing oxygen atoms to fill most of the oxygen defects generated by the excessively high temperature of the first sintering, and at the same time, the more stable rock salt phase reacts very low at this temperature, and the second sintering can retain and solidify the rock salt phase. The rock salt phase has higher resistance to HF corrosion and electrolyte erosion than the LNMO spinel body. The presence of an appropriate amount of rock salt phase can slow down the dissolution of Mn, which is beneficial to improving the stability of Mn in LNMO and improving the cycle and storage performance of the battery prepared from the positive electrode material.
[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium nickel manganese oxide positive electrode material, characterized in that: The method comprises the following steps: mixing a nickel manganese precursor with a lithium source and a dopant, and then performing a first sintering to obtain lithium nickel manganese oxide containing a rock salt phase; jet milling the lithium nickel manganese oxide containing a rock salt phase to obtain lithium nickel manganese oxide single crystal fine powder; and performing a second sintering on the lithium nickel manganese oxide single crystal fine powder to obtain a lithium nickel manganese oxide positive electrode material; The chemical formula of the nickel-manganese precursor is Ni 0.25 Mn 0.75 (OH)2; the chemical formula of the rock salt phase is Li m Ni 1-m O, where 0<m<1; The dopant is selected from at least one of ZrO2, Cr2O3 and Y2O3, and the mass of the dopant is 0.5% to 5% of the nickel-manganese precursor; The first sintering is carried out at 1000℃~1200℃ for 8h~15h; the atmosphere of the first sintering is air; The particle size of the lithium nickel manganese oxide single crystal fine powder obtained after jet milling is D 50 5μm~7μm; The second sintering is carried out at 700°C~900°C for 1h~10h; the atmosphere of the second sintering is air.
2. The preparation method according to claim 1, characterized in that: The ratio of the molar amount of Li in the lithium source to the total molar amount of Ni and Mn in the nickel-manganese precursor is 0.5:1 to 0.55:
1.
3. The preparation method according to claim 2, characterized in that: The lithium source is lithium carbonate.
4. The preparation method according to claim 1, characterized in that: In the lithium nickel manganese oxide containing the rock salt phase obtained by the first sintering, the mass percentage of the rock salt phase is 2wt%~10wt%.
5. The preparation method according to claim 1, characterized in that: The jet milling is carried out under the conditions of a classification frequency of 115 Hz to 125 Hz and a pressure of 0.40 MPa to 0.50 MPa.
6. A lithium nickel manganese oxide positive electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5; In the lithium nickel manganese oxide positive electrode material, the rock salt phase is solidified on the surface of the lithium nickel manganese oxide single crystal fine powder.
7. A battery, characterized in that: The battery contains the lithium nickel manganese oxide positive electrode material according to claim 6.
Citation Information
Patent Citations
Spinel lithium nickel manganese oxide material and preparation method thereof
CN117321798A
Positive electrode active material and preparation method thereof, positive electrode plate, secondary battery and electric device
CN118738374A